2018
DOI: 10.1080/09540121.2018.1441969
|View full text |Cite
|
Sign up to set email alerts
|

Association between coping strategies, social support, and depression and anxiety symptoms among rural Ugandan women living with HIV/AIDS

Abstract: Poor mental health detrimentally affects quality of life among women living with HIV/AIDS. An improved understanding of how coping and social support relate to depression and anxiety in this population can facilitate the design and implementation of appropriate mental health treatment and support services. Secondary analysis was conducted on baseline data from 288 HIV-positive women enrolled in a parenting intervention in Uganda. Depression and anxiety symptoms, social support, and coping were assessed with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 59 publications
2
31
0
Order By: Relevance
“…In addition, neurodevelopmental delay in prenatally HIV‐exposed children may be caused by many environmental and socioeconomic differences in their families 26 . Low socioeconomic status, pervasive poverty, nutritional hardship, level of education, and poor caregiving place these children at greatest neurodevelopmental risk 27,28 . Here, we also explored potential socioeconomic confounders to MDI and PDI scores of children, including home style, family income, feeding mode, place of residence, and parents' occupation and degree of education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, neurodevelopmental delay in prenatally HIV‐exposed children may be caused by many environmental and socioeconomic differences in their families 26 . Low socioeconomic status, pervasive poverty, nutritional hardship, level of education, and poor caregiving place these children at greatest neurodevelopmental risk 27,28 . Here, we also explored potential socioeconomic confounders to MDI and PDI scores of children, including home style, family income, feeding mode, place of residence, and parents' occupation and degree of education.…”
Section: Discussionmentioning
confidence: 99%
“…26 Low socioeconomic status, pervasive poverty, nutritional hardship, level of education, and poor caregiving place these children at greatest neurodevelopmental risk. 27,28 Here, we also explored potential socioeconomic confounders to MDI and PDI scores of children, including home style, family income, feeding mode, place of residence, and parents' occupation and degree of education. We found that the difference of MDI score between HEU children and HUU children might be associated with the number of family children, type of delivery, baby's place of residence, feeding styles, and father's or mother's degree of education.…”
Section: Multivariate Stepwise Logistic Regression Analysis Of Developmental Levelmentioning
confidence: 99%
“…Thus, having good support was found to be an essential coping mechanism for adjustment and act as a buffer towards stress in mental and physical health (Hostinar & Gunnar, 2015). Positive social support lowered the risk of getting depression and in contrast, less support associated with a higher score of depressive symptoms (Fawzi et al, 2012;Seffren et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The relationship between adaptation and preferred coping strategies was covered by numerous studies involving various groups: students (Heffer & Willoughby, 2017;Kozhukhar, 2017;Smith & Yang, 2017), cancer patients (Kaliampos & Roussi, 2017;Knowles et al, 2017;Zadeh et al, 2018), depression patients (Drapeau et al, 2017), multiple sclerosis patients (Grech et al, 2018), people discriminated against on racial grounds ( Levy et al, 2016;Park et al, 2018), and women with HIV/AIDS (Seffren et al, 2018).…”
Section: Strategic Coping and Personal Adjustmentmentioning
confidence: 99%